SUPER VII. morphology and kinematics of H α emission in AGN host galaxies at cosmic noon using SINFONI. Issue 4 (9th February 2023) - Kakkad, D; Mainieri, V; Vietri, G; Lamperti, I; Carniani, S; Cresci, G; Harrison, C; Marconi, A; Bischetti, M; Cicone, C; Circosta, C; Husemann, B; et al.
ABSTRACT: We present spatially resolved H α properties of 21 type 1 AGN host galaxies at z ∼ 2 derived from the SUPER survey. These targets were observed with the adaptive optics capabilities of the SINFONI spectrograph, a near-infrared integral field spectrograph, that provided a median spatial resolution of 0.3 arcsec (∼2 kpc). We model the H α emission line profile in each pixel to investigate whether it traces gas in the narrow line region or if it is associated with star formation. To do this, we first investigate the presence of resolved H α emission after subtracting the AGN PSF. We find extended H α emission in 16 out of the 21 type 1 AGN host galaxies (76 per cent). Based on the BPT diagnostics, optical line flux ratios and line widths (FWHM), we show that the H α emission in five galaxies is ionized by the AGN (30 per cent), in four galaxies by star formation (25 per cent) and for the rest (45 per cent), the ionization source is unconstrained. Two galaxies show extended H α FWHM >600 km s −1, which is interpreted as a part of an AGN-driven outflow. Morphological and kinematic maps of H α emission in targets with sufficient signal-to-noise ratio suggest the presence of rotationally supported discs in six galaxies and possible presence of companions in four galaxies. In two galaxies, we find an anticorrelation between the locations of extended H α emission and [O iii ]-based ionized outflows, indicating possible negative feedback at play. However, in the majority of galaxies, we do not find evidence of outflows impacting H α-based star formation.